Conversion of waste polypropilene (pp) using the zeolite Ni/ZSM-5 to liquid fuel - Thahir, Ramli; Kusuma, Imam Fatwa; Aprilia, Nursyam; Alam, Ahmad Noor; Halim, Abd; Alwathan, Alwathan; Marlinda, Marlinda; Kurniawan, Andri; Puspasari, Febriyati; Rahman, Abdul; Irwan, Muh (Konversi, 2023)
Fuel oil from plastic waste is a promising alternative fuel because of its carbon chaincharacteristics and physical properties which is similar to the crude oil. In addition, the demand for plastic is still increasing which eventually becomes plastic waste. The aim of this study was to determine the quality and application of liqui0d oil produced by pyrolysis catalytic cracking assisted Ni/ZSM-5 from polypropylene (PP) plastic waste. The obtained products were liquid, gas, and char. The optimal yield of fuel oil at 390oC was 239 ml of fuel oil/250 g of PP with a conversion of 79.20 %,wt (72%, liquid and 7.20% gas) and the remaining product was char. The characteristics of the fuel oil products are in the range of gasoline and kerosene fuel types. The average yield value of oAPI in the range of 51-42 for kerosene-type fuel in trays 1 and 2. Furthermore, gasoline-type fuel was resulted in trays 3 and 4 with oAPI value in the range of 52-63.